The competitive landscape of high-frequency trading firms - BOEHMER, Ekkehart (Institutional Knowledge at Singapore Management University, 2018)
We examine product differentiation in the high-frequency trading (HFT) industry, where the “products” are secretive proprietary trading strategies. We demonstrate how principal component analysis can be used to detect underlying strategies that are common to multiple HFT firms, and show that there are three product categories with distinct attributes. We study how HFT competition in each product category impacts the market environment, presenting evidence that indicates how it influences the short-horizon volatility of stocks as well as the viability of trading venues.